2011
DOI: 10.1158/1078-0432.ccr-10-2273
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Cetuximab-Based Neoadjuvant Radiochemotherapy in Locally Advanced Rectal Cancer

Abstract: Purpose: Phase II trials in locally advanced rectal cancer have shown that cetuximab-based neoadjuvant radiochemotherapy is feasible but without an improvement in complete pathologic response rates. Our goal was to identify patients who would benefit from cetuximab-based neoadjuvant chemoradiation measuring gene expression levels of proteins involved in tumor growth [endothelial growth factor receptor (EGFR)], angiogenesis [VEGF, VEGF receptors 1 and 2 (VEGFR1, VEGFR2)], DNA repair [excision repair cross-compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 32 publications
4
24
0
1
Order By: Relevance
“…In particular, no patients with a BRAF , NRAS , APC , or TP53 mutation achieved a pCR, and only one patient with a combined KRAS/PIK3CA mutation had a pCR. Similarly, others have shown that mutations in KRAS predict for lack of pCR and p53 wild type to be predictive of pCR [9, 10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, no patients with a BRAF , NRAS , APC , or TP53 mutation achieved a pCR, and only one patient with a combined KRAS/PIK3CA mutation had a pCR. Similarly, others have shown that mutations in KRAS predict for lack of pCR and p53 wild type to be predictive of pCR [9, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified clinical and biologic predictors of pCR, including a longer interval from completion of CRT to surgery, pre- and post-CRT carcinoembriogenic antigen (CEA) levels, KRAS status, and expression of EGFR or VEGF [710]. We sought to assess both clinical and biologic predictors of pCR, focusing specifically on targetable genetic mutations in order to identify patients who may benefit from more intensive or alternative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These referenced studies have been conducted in accordance with the Declaration of Helsinki (1964) and the protocols of these studies have the EGFR pathway is activated, the tumour phenotype becomes more aggressive and may acquire resistance to treatments 22 . RAS oncogenes have a well-established role in cell growth and proliferation, with its three isoforms, mainly neuroblastoma rat sarcomal viral oncogene homologue (NRAS) KRAS and Harvey rat sarcoma viral oncogene homologue (HRAS).…”
Section: Discussionmentioning
confidence: 99%
“…Several correlative studies attempted to elicit molecularly defined subgroups that may benefit from the addition of cetuximab. However, thus far, no single marker or pattern of markers, including EGFR, KRAS, BRAF, PTEN, etc., could be unambiguously identified to have predictive or prognostic value [16,20,21]. One common feature of all the clinical trials reported so far is that the primary endpoint chosen to assess the efficacy of CRT with EGFR inhibitors was the early surrogate endpoint pCR.…”
Section: Integrating Targeted Agents Into the Combined Modality Programmentioning
confidence: 99%